2014
DOI: 10.1016/j.rasd.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder (AD/HD) in autism spectrum disorder

Abstract: The purpose of this review is to provide an overview of the research on AttentionDeficit/Hyperactivity (AD/HD) in individuals with autism spectrum disorder (ASD). Topics explored are the prevalence of AD/HD, the importance of studying AD/HD, as well as the questionnaire measures used to measure AD/HD in individuals with ASD. Research on the relationship between AD/HD in ASD and parental stress and psychological distress, developmental regression, language and communication, adaptive behavior, social skills, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Common comorbidities in ASD include gastrointestinal (GI) symptoms, sleep problems, attention-deficit/hyperactivity disorder (AD/HD), epilepsy, anxiety, toileting problems, feeding problems, emotional and behavioural problems, selfinjury, aggression and tantrum behaviour (Devlin et al 2008;Mannion & Leader 2013, 2014a, 2014bMaskey et al 2013;Leader & Mannion 2016a;Francis et al 2017;Leader et al 2020). Research has identified comorbidities in other rare genetic conditions such as fragile X syndrome (Newman et al 2015).…”
Section: Duplication 15q Syndrome and Comorbiditymentioning
confidence: 99%
“…Common comorbidities in ASD include gastrointestinal (GI) symptoms, sleep problems, attention-deficit/hyperactivity disorder (AD/HD), epilepsy, anxiety, toileting problems, feeding problems, emotional and behavioural problems, selfinjury, aggression and tantrum behaviour (Devlin et al 2008;Mannion & Leader 2013, 2014a, 2014bMaskey et al 2013;Leader & Mannion 2016a;Francis et al 2017;Leader et al 2020). Research has identified comorbidities in other rare genetic conditions such as fragile X syndrome (Newman et al 2015).…”
Section: Duplication 15q Syndrome and Comorbiditymentioning
confidence: 99%
“…Autism spectrum disorder (ASD) and ADHD are both childhood neurodevelopmental conditions that share common features including social interaction deficits, emotion regulation difficulties, and behavior concerns (for review, see Mannion & Leader, 2014; Matson, Rieske, & Williams, 2013). When a child displays several of these concerns, both ASD and ADHD are possible options for explaining the child’s presentation.…”
mentioning
confidence: 99%
“…In contrast, ADHD is characterized by greater manifestations of inattention, impulsivity, and hyperactivity than what would be expected for the individual's developmental level. However, these two disorders also share various characteristics (see Mannion & Leader, 2014): Their diagnoses are based on behavioral symptoms (American Psychiatric Association [APA], 2013); they both involve the presence of communication and attention problems (Hattori et al…”
mentioning
confidence: 99%
“…In contrast, ADHD is characterized by greater manifestations of inattention, impulsivity, and hyperactivity than what would be expected for the individual’s developmental level. However, these two disorders also share various characteristics (see Mannion & Leader, 2014): Their diagnoses are based on behavioral symptoms (American Psychiatric Association [APA], 2013); they both involve the presence of communication and attention problems (Hattori et al, 2006; Martin, Hamshere, O’Donovan, Rutter, & Thapar, 2014), deficits in social skills (Demopoulos, Hopkins, & Davis, 2013), and difficulties in some aspects of executive functioning (Miranda-Casas, Baixauli-Fortea, Colomer-Diago, & Roselló-Miranda, 2013; Yerys et al, 2009); and there even seems to be some overlap in their genetic origin (Rommelse, Franke, Geurts, Hartman, & Buitelaar, 2010; Ronald, Simonoff, Kuntsi, Asherson, & Plomin, 2008).…”
mentioning
confidence: 99%